Altered sleep and neurovascular dysfunction in alpha-synucleinopathies: the perfect storm for glymphatic failure - Buongiorno, Mariateresa; Marzal, Clara; Fernandez, Manel; Cullell, Natalia; de Mena, Lorena; Sánchez-Benavides, Gonzalo; de la Sierra, Alejandro; Krupinski, Jerzy; Compta, Yaroslau (Frontiers in Aging Neuroscience, 2023)
Clinical and cognitive progression in alpha-synucleinopathies is highly heterogeneous. While some patients remain stable over long periods of time, other suffer early dementia or fast motor deterioration. Sleep disturbances and nocturnal blood pressure abnormalities have been identified as independent risk factors for clinical progression but a mechanistic explanation linking both aspects is lacking. We hypothesize that impaired glymphatic system might play a key role on clinical progression. Glymphatic system clears brain waste during specific sleep stages, being blood pressure the motive force that propels the interstitial fluid through brain tissue to remove protein waste. Thus, the combination of severe sleep alterations, such as REM sleep behavioral disorder, and lack of the physiological nocturnal decrease of blood pressure due to severe dysautonomia may constitute the perfect storm for glymphatic failure, causing increased abnormal protein aggregation and spreading. In Lewy body disorders (Parkinson’s disease and dementia with Lewy bodies) the increment of intraneuronal alpha-synuclein and extracellular amyloid-β would lead to cognitive deterioration, while in multisystemic atrophy, increased pathology in oligodendroglia would relate to the faster and malignant motor progression. We present a research model that may help in developing studies aiming to elucidate the role of glymphatic function and associated factors mainly in alpha-synucleinopathies, but that could be relevant also for other protein accumulation-related neurodegenerative diseases. If the model is proven to be useful could open new lines for treatments targeting glymphatic function (for example through control of nocturnal blood pressure) with the objective to ameliorate cognitive and motor progression in alpha-synucleinopathies.